PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN GO-JEK - Ridwan, Muhammad; Noviyanti, Sintya (Kinerja, 2021)
This study is to determine the effect of Service Quality and Customer Satisfaction on Customer Loyalty the sample used is 96 consumers. Hypothesis testing uses validity and reliability tests, especially classiﬁcation assumptions such as normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The analysis used is regression and correlation analysis, determination, t test and f test, based on the results of research partially showing that service quality has a positive and significant influence on Gojek Customer Loyalty with a significance of 0.000 <0.05 and a tcount of 3.762 and for customer satisfaction. Partially also shows that customer satisfaction has a positive and significant influence on Gojek Customer Loyalty, which is significant 0.001 <0.05 and tcount is 3.568. Meanwhile, the results of the simultaneous test show that service quality and customer satisfaction have a simultaneous effect on gojek customer loyalty